Pattern of bear maul injuries in tertiary hospital in Nepal: demographic, management and outcome - Rayamajhi, Sangam; KC, K; Shrestha, JM; Lohani, I (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Nepal is a country full of forests and with increase in urbanization there is encroachment into the territories of wild animals. Their encounters have been in the rise and bear maul seem to be one of the leading cause of wild animal attacks. The injuries are very disastrous and leave behind permanent disfigurements and disabilities. Methods: All of cases of bear maul treated in TU Teaching Hospital for the last 6 year were studied. Analysis of pattern and severity of the injuries were done along with the complication and its morbidities. Results: Total of 17 cases was studied. Majority of the cases were male and at age of 20 to 40 years. All but one were sudden attack by Himalayan black bear (15 cases) using their claws (in 17 cases) mostly to the face (16 cases), eyes (10 cases) and scalp (8 cases) resulting in fractures (14 cases). There were more proportion of patient with the complex wounds (10 cases) requiring initial debridement followed by closure with graft (5 cases), flap (5 cases) or free flaps (1 case) than the simple wounds which were just debridement and closed with primary (5 cases) or secondary sutures (2 cases). All patients were left with ugly scar and majority had facial disfigurements (12 cases) with major contour deformities (7 cases). Four patients had permanent vision loss in one eye. Conclusion: The rising trend of bear maul injuries, are complex injuries requiring prompt multidisciplinary approach of management. Face and eyes are the most common sites of injuries and often associated with underlying fractures. Bear maul though rarely fatal, leaves permanent disfigurement and disabilities. JSSN 2015; 18 (1), Page: 17-22